Intercalation of Li Atoms in TaSe2 Film’s Anode with LiClO4/PEO Polymer Electrolyte: First Principles Calculation - Prikhozha, Yu. O.; Balabai, R.M. (Physics and Chemistry of Solid State, 2022)
Using the methods of electron density functional and pseudopotential from the first principles, the total energy, energy reliefs and migration barriers of Li atoms in the interlayer space of layers of anode material made of 2H-TaSe2, 2H-TaSe2 with molecules of polymer electrolytes LiClO4, PEO and LiClO4/PEO, charges on Se atoms limit the interlayer space2H-TaSe2, spatial distributions of valence electron density and their cross sections.